1996
DOI: 10.1183/09031936.96.09010117
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of clinical features for the obstructive sleep apnoea syndrome

Abstract: The advantage of being a National Referral Centre for patients with suspected obstructive sleep apnoea (OSA) was used to seek clinical factors predictive of OSA, and thus determine if the number of polysomnography tests required could be reduced. Patients were mainly primary referrals, from an island population of 3.5 million.Two hundred and fifty consecutive patients underwent clinical assessment, full polysomnography, and a detailed self-administered questionnaire. This represents one of the largest European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
131
2
23

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(160 citation statements)
references
References 25 publications
4
131
2
23
Order By: Relevance
“…1,[30][31][32][33] In adults, OSA is linked to obesity. [34][35][36][37][38] In a prospective evaluation of adults, NC corrected for height was actually a better predictor of OSA than symptoms or general obesity, as assessed by body mass index (BMI). This implies that the relationship between OSA and obesity is dependent on the variation in NC and suggests that central fat deposition in the neck and viscera is more contributory than generalized adiposity 38,39 to OSA development.…”
Section: Discussionmentioning
confidence: 99%
“…1,[30][31][32][33] In adults, OSA is linked to obesity. [34][35][36][37][38] In a prospective evaluation of adults, NC corrected for height was actually a better predictor of OSA than symptoms or general obesity, as assessed by body mass index (BMI). This implies that the relationship between OSA and obesity is dependent on the variation in NC and suggests that central fat deposition in the neck and viscera is more contributory than generalized adiposity 38,39 to OSA development.…”
Section: Discussionmentioning
confidence: 99%
“…Those models differ in terms of the variables included and the case definitions, making it difficult to compare the results across studies. (12,13,27,28) The use of multiple regression analyses with the inclusion of clinical variables has produced good prediction models. In a prospective study evaluating four AHI prediction models, their sensitivity was found to be high (85-98%), although their specificity was low (33-39%).…”
Section: Discussionmentioning
confidence: 99%
“…(11) The clinical impression alone has low accuracy for the diagnosis of sleep-disordered breathing, and polysomnography therefore remains indispensable. (12,13) A meta-analysis of clinical studies for the diagnosis of obstructive sleep apnea revealed that clinical models have higher OR values for diagnosis and severity than do questionnaire-based models (10.49 and 17.24 vs. 5.02 and 10.12, respectively). (14) In that study, the clinical elements associated with an OR > 2 were BMI, arterial hypertension, and a history of nocturnal choking.…”
mentioning
confidence: 99%
“…[5][6][7][8] However, there has been related work on the prediction of sleep disordered breathing and RDI. For example, a recent review of prediction formulas for severe sleep disordered breathing (RDI ≥ 20/h) reported sensitivities varying between 76% and 96% and specificities varying between 13% and 54%.…”
Section: In the Routine Clinical Evaluation Of Patients For Possible mentioning
confidence: 99%